A critical review of histopathological findings associated with endocrine and non-endocrine hepatic toxicity in fish models - Wolf, Jeffrey C.; Wheeler, James R. (Aquatic toxicology, 2018)
Although frequently examined as a target organ for non-endocrine toxicity, histopathological evaluation of the liver is becoming a routine component of endocrine disruption studies that utilize various fish species as test subjects. However, the interpretation of microscopic liver findings can be challenging, especially when attempting to distinguish adverse changes associated with endocrine disrupting substances from those caused by systemic or direct hepatic toxicity. The purpose of this project was to conduct a critical assessment of the available peer-reviewed and grey literature concerning the histopathologic effects of reproductive endocrine active substances (EAS) and non-endocrine acting substances in the livers of fish models, and to determine if liver histopathology can be used to reliably distinguish endocrine from non-endocrine etiologies. The results of this review suggest that few compound-specific histopathologic liver effects have been identified, among which are estrogen agonist-induced increases in hepatocyte basophilia and proteinaceous intravascular fluid in adult male teleosts, and potentially, decreased hepatocyte basophilia in female fish exposed to substances that possess androgenic, anti-estrogenic, or aromatase inhibitory activity. This review also used published standardized methodology to assess the credibility of the histopathology data in each of the 117 articles that reported liver effects of treatment, and consequently it was determined that in only 37% of those papers were the data considered either highly credible or credible. The outcome of this work highlights the value of histopathologic liver evaluation as an investigative tool for EAS studies, and provides information that may have implications for EAS hazard assessment.